Exact solutions to the perturbed nonlinear Schrödinger’s equation with Kerr law nonlinearity by using the first integral method - Moosaei, Hossein; Mirzazadeh, Mohammad; Yildirim, Ahmet (Nonlinear Analysis: Modelling and Control, 2011)
The first integral method is an efficient method for obtaining exact solutions of some nonlinear partial differential equations. In this paper, the first integral method is used to construct exact solutions of the perturbed nonlinear Schrodinger’s equation (NLSE) with Kerr law nonlinearity. It is shown that the proposed method is effective and general.